The Role of Corporate Governance in Mediating the Effect of Corporate Social Responsibility and Green Innovation on the Business Performance of the Ikait Woven Fabric Creative Industry - Rupilu, Wilsna; Wulandari, Agusta Amanda; Gah, Tiffany Natalia Petronela (Borong Newinera Publisher, 2026)
The purpose of this study is to examine the role of corporate governance in mediating the effect of corporate social responsibility and green innovation on the business performance of the Ikat woven fabric creative industry in East Nusa Tenggara (NTT). The findings are expected to help the creative industry enhance its competitiveness by not only focusing on business sustainability and profitability through Good Corporate Governance (GCG) and Green Product Innovation (GPI), but also by considering the surrounding community through Corporate Social Responsibility (CSR). This study employed a quantitative explanatory research design. The data source consisted of primary data. The population included creative industry actors in the Ikat woven fabric sector across Flores Island, specifically in West Manggarai Regency, Manggarai, Sikka, and Ende. The sample was selected using quota and purposive sampling techniques, resulting in 55 creative industry actors. Data were analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS). The results indicate that corporate social responsibility has a positive and significant effect on business performance. Green innovation also has a positive and significant effect on business performance. Furthermore, corporate social responsibility has a positive and significant effect on business performance through good corporate governance as a mediating variable. Similarly, green innovation has a positive and significant effect on business performance through good corporate governance.